2023
DOI: 10.1002/pc.27263
|View full text |Cite
|
Sign up to set email alerts
|

Aramid fiber coated with aramid nanofiber coating to improve its interfacial properties with polycarbonate

Abstract: This study addresses the effect of the coatings prepared from aramid nanofibers (ANFs) on the surface treatment of aramid fiber and reinforced polycarbonate (PC) composite (AF/PC). Aramid fiber's smooth, inert surface bonds poorly with polycarbonate. In this research, the PC‐ANF coating was made by the PC/CH2Cl2 solution, which was modified by aramid nanofibers to improve the interfacial adhesion and compatibility of aramid fiber/PC composites. What's more, the silane (KH570) was added to improve the dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…BPPTA compared to the neat PAN nanofiber mat, indicating a promising improvement in stiffness and then decreased with further BPPTA loading. The strong intermolecular interactions between the matrix and the additive polymer molecules result in improved mechanical and thermal properties due to the effective load transfer as well as the enhanced interfacial adhesion and connectivity of the resulting network 40,76,78 . However, after an optimal filling ratio, over‐fusion of the nanofibers may have negative effects on the tensile and flexural properties 85 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BPPTA compared to the neat PAN nanofiber mat, indicating a promising improvement in stiffness and then decreased with further BPPTA loading. The strong intermolecular interactions between the matrix and the additive polymer molecules result in improved mechanical and thermal properties due to the effective load transfer as well as the enhanced interfacial adhesion and connectivity of the resulting network 40,76,78 . However, after an optimal filling ratio, over‐fusion of the nanofibers may have negative effects on the tensile and flexural properties 85 .…”
Section: Resultsmentioning
confidence: 99%
“…The strong intermolecular interactions between the matrix and the additive polymer molecules result in improved mechanical and thermal properties due to the effective load transfer as well as the enhanced interfacial adhesion and connectivity of the resulting network. 40,76,78 However, after an optimal filling ratio, over-fusion of the nanofibers may have negative effects on the tensile and flexural properties. 85 While the increase in mechanical performance is expected to continue due to the decrease in average fiber diameter and increase in inter-chain interactions as the additive ratio increases, it is observed that the mechanical properties decrease with additive loading higher than an optimal filling ratio, which is 3%, 5%, and 1% for tensile strength, toughness, and elastic modulus, respectively.…”
Section: Mechanical Properties Of the Cnmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Para‐aramid fibers are high‐performance fibers composed of highly oriented and rigid poly(terephthaloyl‐p‐phenylenediamine) with strong hydrogen bonding which exhibits considerably high strength and modulus, acid and alkali resistance, durability, flame, and heat resistance 1–5 . Para‐aramid paper, which is normally prepared with aramid chopped fibers (ACFs) and fibrid or pulp fiber by wet papermaking and hot‐pressing, 6–8 is widely used in national defense, aerospace, electromechanical components, automotive parts, high‐temperature fume filtration, and other areas 9–15 .…”
Section: Introductionmentioning
confidence: 99%
“…ANFs may also improve the interfacial properties of aramid materials. 21 With the help of ANF, ZnO nanoparticles can be better incorporated into aramid materials. The combination of ANF and nanomaterials could be achieved more easily, thanks to the nanoscale dimension and the higher number of active functional groups of ANF.…”
Section: Introductionmentioning
confidence: 99%